(untitled) (Journal of Comparative & International Higher Education, 2024)
This paper examines whether participating in a five-week asynchronous video exchange program would affect the intercultural competence of undergraduate students at a university in Japan. Participants collaborated with Taiwanese university students on the topic of sustainable tourism and exchanged self-introduction videos, presentations on local tourism, and feedback. A mixed-methods approach was employed in this study. The Intercultural Competence Scale for University EFL Learners was used to gather quantitative data, and participants’ scores were significantly higher in the post-test in four out of five dimensions. As for qualitative data, a survey with open-ended questions was administered to explore how participants perceived the virtual exchange experience. Several themes emerged including communication, culture, and interpersonal interaction, and participants demonstrated traits related to intercultural competence. Findings in this study have provided evidence to support the positive effects of asynchronous video virtual exchange on cultivating intercultural competence among undergraduate students.